2016
DOI: 10.1111/cea.12673
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity and pathogenic links of chronic spontaneous urticaria and systemic lupus erythematosus – a systematic review

Abstract: Chronic spontaneous urticaria (CSU) is a common mast cell-driven disease characterized by the development of wheals (hives), angioedema (AE), or both for > 6 weeks. It is thought that autoimmunity is a common cause of CSU, which is often associated with autoimmune thyroiditis, whereas the link to other autoimmune disorders such as systemic lupus erythematosus (SLE) has not been carefully explored. Here, we systematically reviewed the existing literature for information on the prevalence of CSU in SLE (and vice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(73 citation statements)
references
References 133 publications
(238 reference statements)
2
69
0
2
Order By: Relevance
“…Approximately 40% of cases of CU are characterized by production of IgG autoantibodies . Chronic spontaneous urticaria and urticarial vasculitis are the two most common underlying causes of CU rash in SLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 40% of cases of CU are characterized by production of IgG autoantibodies . Chronic spontaneous urticaria and urticarial vasculitis are the two most common underlying causes of CU rash in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis and appropriate treatment involving clinicians across many different specialties are crucial for preventing further manifestations and achieving beneficial long‐term outcomes for patients . Urticaria may present as the initial symptom in these patients before the more classical form of SLE is confirmed . CU‐like lesions may occur in lupus tumidus, urticarial plaque of LE, which is an uncommon LE‐specific but distinct subtype of chronic cutaneous LE…”
Section: Introductionmentioning
confidence: 99%
“…These autoantibodies bind to mast cell-bound IgE molecules or surface IgE receptors to stimulate and eventually degranulate the cells and cause the urticarial symptoms [17][18][19]. It was suggested that some CSU patients have an autoimmune mechanism induced by these autoantibodies [20].…”
Section: Comorbidities and Possible Triggering Factorsmentioning
confidence: 99%
“…Thyroid diseases, especially Hashimoto's disease in which production of thyroid autoantibodies (antithyroid peroxidase antibodies and antithyroglobulin antibodies) and lymphocytic infiltration into the thyroid gland are seen, are the most common autoimmune diseases accompanying patients with CSU [19][20][21]. The etiology of thyroid autoimmunity is not known, but the genetic susceptibility and environmental factors are thought to initiate the process [22].…”
Section: Comorbidities and Possible Triggering Factorsmentioning
confidence: 99%
See 1 more Smart Citation